2014
DOI: 10.1038/ismej.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Microbial mediation of biogeochemical cycles revealed by simulation of global changes with soil transplant and cropping

Abstract: Despite microbes’ key roles in driving biogeochemical cycles, the mechanism of microbe-mediated feedbacks to global changes remains elusive. Recently, soil transplant has been successfully established as a proxy to simulate climate changes, as the current trend of global warming coherently causes range shifts toward higher latitudes. Four years after southward soil transplant over large transects in China, we found that microbial functional diversity was increased, in addition to concurrent changes in microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 56 publications
5
77
0
Order By: Relevance
“…All labeled DNA was suspended again in a 10-μl hybridization solution as previously described [29]. Subsequently, DNA was hybridized at 42°C with 40% formamide for 16 hours on a MAUI hybridization station (BioMicro, Salt Lake City, UT, USA) utilizing GeoChip 4.2.…”
Section: Methodsmentioning
confidence: 99%
“…All labeled DNA was suspended again in a 10-μl hybridization solution as previously described [29]. Subsequently, DNA was hybridized at 42°C with 40% formamide for 16 hours on a MAUI hybridization station (BioMicro, Salt Lake City, UT, USA) utilizing GeoChip 4.2.…”
Section: Methodsmentioning
confidence: 99%
“…GeoChip experiments were carried out as previously described (Liu et al 2015;Zhao et al 2014). Briefly, 2 μg DNA was labeled by random primed Cy-5 dye and purified with a QIA quick purification kit (Qiagen, Valencia, CA, USA).…”
Section: Geochip Experimentsmentioning
confidence: 99%
“…Several recent studies have demonstrated that microbial functional genes can be used to indicate rates of environmental processes such as greenhouse gas emission or nitrification potentials Zhao et al, 2014). Although abundance of messenger RNA (mRNA) might be a better indicator of functional activity, the profiling and quantification of mRNA is often difficult due to technical issues of interference from ribosomal RNA (rRNA) and transfer RNA (tRNA), strict transport and storage requirements, rapid turnover and severe instability rendering DNA profiling a more convenient and reliable alternative.…”
Section: Discussionmentioning
confidence: 99%